2009
DOI: 10.1080/10255840903077170
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of hoof landing in horses trotting at high speed and the effects of ground surfaces

Abstract: Recent numerical studies of abdominal aortic aneurysm (AAA) suggest that intraluminal thrombus (ILT) may reduce the stress loading on the aneurysmal wall. Detailed fluid structure interaction (FSI) in the presence and absence of ILT may help predict AAA rupture risk better. Two patients, with varied AAA geometries and ILT structures, were studied and compared in detail. The patient specific 3D geometries were reconstructed from CT scans, and uncoupled FSI approach was applied. Complex flow trajectories within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Other clinical implications may be the development of in vivo imaging methods with molecular probes targeting levels of biological activity of the thrombus. Beside the involvement of the ILT in AAA expansion, it may be kept in mind that some authors by using computerized AAA models have suggested that ILT may also play a beneficial mechanical role in the risk of rupture by reducing AAA wall stress [48,49]. Further studies are thus needed to define more precisely the relative importance of this dual role of the ILT in AAA rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical implications may be the development of in vivo imaging methods with molecular probes targeting levels of biological activity of the thrombus. Beside the involvement of the ILT in AAA expansion, it may be kept in mind that some authors by using computerized AAA models have suggested that ILT may also play a beneficial mechanical role in the risk of rupture by reducing AAA wall stress [48,49]. Further studies are thus needed to define more precisely the relative importance of this dual role of the ILT in AAA rupture.…”
Section: Discussionmentioning
confidence: 99%